2014
DOI: 10.1016/j.jspd.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Method for Determining Transverse Plane Pelvic Obliquity

Abstract: The ability to reliably measure and calculate the degree of transverse plane rotation by radiographs in cerebral palsy patients with spino-pelvic deformity by the method described by Lucas et al. is poor, likely because of difficulty in consistently identify pelvic landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The height between line B and Where Line A and line C meet each other is PO quantity. Zhou et al [3] revealed a simple method, as well as Torretti et al [4], discuss. Their method describes by two lines which one line linked the top of both iliac crests on AP radiography of pelvis and the second was the lowest part of the fourth lumbar vertebra and PO angel de ned where two lines intersect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The height between line B and Where Line A and line C meet each other is PO quantity. Zhou et al [3] revealed a simple method, as well as Torretti et al [4], discuss. Their method describes by two lines which one line linked the top of both iliac crests on AP radiography of pelvis and the second was the lowest part of the fourth lumbar vertebra and PO angel de ned where two lines intersect.…”
Section: Discussionmentioning
confidence: 97%
“…At the same way, Torretti et al perform a study and utilize inferior part of the sacroiliac joint and the lateral edge of anterior superior iliac spine. [4] The aim we are looking for in this study is to de ne a normal range of pelvic obliquity angel by measuring in people who do not have any issues that affect the PO.…”
Section: Introductionmentioning
confidence: 99%
“…The height between line B and the point where line A and line C meet is the PO angle. Zhou et al [ 19 ] revealed a simple method, and Torretti et al [ 15 ], discussed it. Two lines described their method: one line linked the top of both iliac crests on AP pelvis radiography, and the second was the lowest part of the fourth lumbar vertebra, and PO angle defined where two lines intersect.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al describe a slightly different way of measuring PO by using the iliac crest and fourth lumbar vertebra and classifying them into six groups [ 19 ]. Similarly, Torretti et al utilized the inferior parts of the sacroiliac joint and the anterior superior iliac spines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%